First record of Nicobium LeConte (Coleoptera: Ptinidae: Anobiinae) from Baltic amber with the description of a new extinct species - Alekseev, Vitalii; Háva, Jiří; Pankowski, Madeline V.; Bukejs, Andris (Zootaxa, 2024)
The first extinct Paleogene species of the Anobiinae genus Nicobium LeConte, 1861 is described based on an inclusion in Baltic amber. Two characteristic features distinguishing the extinct species (among other characters present in one combination or another in extant species) are sparse, inconspicuous elytral pubescence and rectangular, sharp posterior pronotal angles. The new species, Nicobium necrocrator sp. nov., is just the second described extinct representative of the genus. Its discovery adds to our knowledge of the diversity of deathwatch beetles in the amberiferous forests of the Eocene—and establishes an important reference point for future studies of the origin and distribution of these wood-boring beetles living millions of years ago.